Microcontrollers Performance in Portable Electronic Stethoscope Design with a Disease Symptoms Detection Feature - Torib Hamzah; Endang Dian Setioningsih; Sumber Sumber; Wahyu Caesarendra (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
One of the early examinations that is often done is to detect heart disease using a stethoscope. The electronic stethoscope consists of a membrane and tube from a conventional stethoscope coupled with a condenser microphone which is then connected to a computer. The purpose of this study is to analyze the comparison of two types of microcontrollers in the design of a portable electronic stethoscope equipped with a symptom detector. The research method used is instrumentation with 2 types of microcontrollers to design a heart sound detector. In processing the data to be displayed on the 16x2 Character LCD. Sending heart signal data for 60 seconds to produce BPM data which is processed using 2 different types of microcontrollers. The results of data collection on battery consumption of power usage on the AT mega 2560 resulted in an average saving of 0.11W. Therefore, it can be concluded that the two stethoscopes have a significant difference when compared, where the Arduino Mega 2560 is able to process data from heart signals faster than the AT mega 328P. The results of the research that have been carried out can be implemented using a system that strongly supports the needs when checking heart sound signals